1976
DOI: 10.1002/1097-4679(197610)32:4<896::aid-jclp2270320436>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that suggests a negative association between cigarette smoking and learning performance

Abstract: The results of this study indicate that tobacco smoking may have a deleterious effect on the learning process. One hundred and fifteen male volunteers were assessed on four learning tasks. Those Ss who smoked in excess of 12 cigarettes per day did significantly less well, as a group, than nonsmokers and light smokers on three of the four learning tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Studies which rely on simple, rapidly-paced perceptually-based tasks typically conclude that cigarette smoking facilitates cognitive performance while other evidence (Andersson, 1975;Elgerot, 1976;Gonzales & Harris, 1980;Houston, Schneider & Jarvik, 1978;Kleinman, Vaughn & Christ, 1973;Stevens, 1976;Williams, 1980, for example) suggests that for tasks which depend heavily upon access to long-term memory or manipulation of information in short-term or working memory, nicotine may not facilitate and may even interfere with cognitive performance. A comprehensive review of the literature on smoking and cognition is available to the interested reader (USDHHS, 1988) while a review of methodological considerations for tobacco research is also readily available (Grunberg & Acri, 1991).…”
mentioning
confidence: 99%
“…Studies which rely on simple, rapidly-paced perceptually-based tasks typically conclude that cigarette smoking facilitates cognitive performance while other evidence (Andersson, 1975;Elgerot, 1976;Gonzales & Harris, 1980;Houston, Schneider & Jarvik, 1978;Kleinman, Vaughn & Christ, 1973;Stevens, 1976;Williams, 1980, for example) suggests that for tasks which depend heavily upon access to long-term memory or manipulation of information in short-term or working memory, nicotine may not facilitate and may even interfere with cognitive performance. A comprehensive review of the literature on smoking and cognition is available to the interested reader (USDHHS, 1988) while a review of methodological considerations for tobacco research is also readily available (Grunberg & Acri, 1991).…”
mentioning
confidence: 99%
“…Comparing smokers with nonsmokers to measure the longer term residual effects of smoking status on cognition has been less conclusive. Research has found, for example, that smokers perform more poorly on reaction-time tasks (Knott, 1984; female smokers), immediate memory (Carter, 1974; Gonzales & Harris, 1980), paired associate learning (Kleinman, Vaughn, & Christ, 1973), and free recall (Stevens, 1976). Other studies have reported that smoking status does not affect reaction time (Knott, 1984; male smokers) or delayed recall (Carter, 1974).…”
mentioning
confidence: 99%
“…The remaining three studies were more heterogeneous, and explored different facets of memory and learning. Stevens (1976) found that heavy smokers performed worse on different learning tests. Tait et al (2000) found that there were no substantial differences between the groups on visual memory, but heavy smokers displayed deficits while experiencing nicotine deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…There were five studies that investigated the role of memory or learning. Stevens (1976) performed an early study comparing non-smokers, light smokers, and heavy smokers on several complex learning tasks. These included the Hunter-Pascal Concept task, the Wisconsin Card Sorting task, the Standard Anagram task, and the Word-in-Context test.…”
Section: Memory Networkmentioning
confidence: 99%
See 1 more Smart Citation